Dissecting carboxypeptidase E: properties, functions and pathophysiological roles in disease. Issue 4 (May 2017) - Ji, Lin; Wu, Huan-Tong; Qin, Xiao-Yan; Lan, Rongfeng
Abstract : Since discovery in 1982, carboxypeptidase E (CPE) has been shown to be involved in the biosynthesis of a wide range of neuropeptides and peptide hormones in endocrine tissues, and in the nervous system. This protein is produced from pro-CPE and exists in soluble and membrane forms. Membrane CPE mediates the targeting of prohormones to the regulated secretory pathway, while soluble CPE acts as an exopeptidase and cleaves C-terminal basic residues from peptide intermediates to generate bioactive peptides. CPE also participates in protein internalization, vesicle transport and regulation of signaling pathways. Therefore, in two types of CPE mutant mice, Cpe fat /Cpe fat and Cpe knockout, loss of normal CPE leads to a lot of disorders, including diabetes, hyperproinsulinemia, low bone mineral density and deficits in learning and memory. In addition, the potential roles of CPE and ΔN-CPE, an N-terminal truncated form, in tumorigenesis and diagnosis were also addressed. Herein, we focus on dissecting the pathophysiological roles of CPE in the endocrine and nervous systems, and related diseases.